Protistal Grazers Increase Grazing on Unicellular Cyanobacteria Diazotroph at Night - Deng, Lixia; Cheung, Shunyan; Liu, Hongbin (Frontiers in Marine Science, 2020)
In this study, we have for the first time analyzed diel microzooplankton grazing selectivity on unicellular cyanobacterial diazotroph (i.e., Crocosphaera watsonii WH8501) and non-diazotrophic unicellular microalga (i.e., Chlorella autotrophica). A mixed diet consisting of these two phytoplankton was supplied to four species of protistal grazers during daytime and nighttime, respectively. C. watsonii fixes nitrogen during nighttime and showed a stronger diel pattern of cellular C:N ratio than C. autotrophica. All four grazers ingested more nighttime C. watsonii than daytime C. watsonii, suggesting the diazotroph became more nutritious (inferred by C:N ratio) and thus a preferred prey for grazers when it fixes nitrogen. In particular, Oxyrrhis marina changed from preferring C. autotrophica during daytime to preferring C. watsonii during nighttime. The rest grazers showed species-specific grazing preferences, which could be explained by extracellular polysaccharide production of C. watsonii, feeding mode, cingulum size and cell size of grazers.